Change in the Electrochemical Parameters and Material Conductivity During Cycling of Electrochemical Cells with Cathodes Based on MgF2 - I.M. Gasyuk; М.Ja. Sichka; V.V. Ugorchuk; L.S. Kaykan; А.М. Bojchuk (Журнал нано- та електронної фізики)
The paper deals with the properties of the lithium power source cathodes made on the basis of MgF2. Researches were conducted using the following electrochemical methods: galvanostatic cycling, cyclic voltammetry, electrochemical impedance spectroscopy. Much attention has been attracted to changing the electrochemical parameters (specific discharge capacity, Coulomb efficiency, coefficient of electrostimulated diffusion). We have studied the dynamics of the leading characteristics of the cathode material during cycling of electrochemical cell models.